Natur Antropologi: Memahami Keragaman Potensi Humanitas Dalam Konteks Komparatif Dengan Perspektif Kristen - Stenly R. Paparang (STT Pelita Dunia, 2018)
Abstract: This article looks at the anthropology of how humans understand and assess the ins and outs of life, and draws conclusions to be used as a guide for life in shaping moral, spiritual, comfort, peace, relationships, credibility, and legacy. Anthropology talks about a series of events in human (social) groups and the changes that occur which can be inherited or substantially revised, reinterpreted, and taken as an